2021
DOI: 10.1155/2021/4964195
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of Suture Anchor and Double-Pulley Technique in the Treatment of Inferior Patellar Fracture

Abstract: Objective. To evaluate the efficacy of suture anchor combined with double-pulley technique for subpatellar comminuted fractures compared with wire vertical suture and Krachow in the treatment of subpatellar fractures. Methods. Retrospectively selected 48 patients with subpatellar pole comminuted fracture admitted in our hospital from February 2013 to July 2019, 25 patients with double-pulley technique (group A), and 23 patients with vertical wire suture with Krachow suture. Patient age, gender, AT/OTA typing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…None of the 16 identified studies performed a direct comparison between the KT and VW techniques. Eight studies 5,7,9,[15][16][17]27,28 involving 132 inferior pole fractures of the patella evaluated the results of the KT technique, while 8 studies 3,8,10,11,18,[29][30][31] involving 142 inferior fractures of the patella evaluated the results of the separate VW technique. All included studies had a minimum of 6 months of follow-up, and 9 5,8,11,15,17,18,[29][30][31] had a minimum of 1 year of follow-up (Table 1).…”
Section: Study Characteristics and Methodological Quality Assessmentmentioning
confidence: 99%
“…None of the 16 identified studies performed a direct comparison between the KT and VW techniques. Eight studies 5,7,9,[15][16][17]27,28 involving 132 inferior pole fractures of the patella evaluated the results of the KT technique, while 8 studies 3,8,10,11,18,[29][30][31] involving 142 inferior fractures of the patella evaluated the results of the separate VW technique. All included studies had a minimum of 6 months of follow-up, and 9 5,8,11,15,17,18,[29][30][31] had a minimum of 1 year of follow-up (Table 1).…”
Section: Study Characteristics and Methodological Quality Assessmentmentioning
confidence: 99%
“…21 This procedure is minimally invasive, restores the anatomy of the knee extensor mechanism, and avoids the need for secondary surgery. 22 However, Kadar et al reported internal fixation failure due to limited fixation strength with wire anchors. The reoperation rate was 14.8%, with a high infection rate (11%), 19 Also, the placement of a wire anchor nail after partial resection of the inferior pole bone may decrease patellar height and cause misalignment.…”
Section: Current Clinical Trendsmentioning
confidence: 99%
“…The main principle is to bury a screw proximal to the patellar fracture, and then insert an anchor nail with its own tail wire through the patellar ligament to reposition the fracture and soft tissue at the lower pole of the patella and restore the original anatomical shape 21 . This procedure is minimally invasive, restores the anatomy of the knee extensor mechanism, and avoids the need for secondary surgery 22 . However, Kadar et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary goal of treating patellar inferior pole fractures is to restore the knee extension mechanism. Improper treatment of these fractures may result in the loss of the knee extension mechanism and patellofemoral joint coordination [ 4 , 5 ]. Therefore, anatomical reduction with strong internal fixation and early rehabilitation are important for patellar inferior pole fractures.…”
Section: Introductionmentioning
confidence: 99%